Virtual professional development for freelance indexers: potential, pitfalls and practicalities. (1st June 2021) - Kingdom, Ann
Abstract : For freelance book indexers, an important part of their continuing professional development (CPD) has been through the conferences and workshops run by their national societies, providing a welcome break from the isolation of working from home, as well as opportunities to hone skills, learn new ones and generally keep abreast with developments in the profession. As COVID-19 spread rapidly round the globe, events began to be cancelled and the indexing community (like many professions) was forced to move online, quickly adapting to the new situation. A survey of freelance indexers who have participated in online CPD, together with the questionnaire responses of those involved in organizing and delivering these events, identifies good practice and shows that they have several advantages over face-to-face events. In some cases they are also filling a previously unmet need. There is no doubt that online events will become a permanent part of the mix of opportunities for professional development in a post-pandemic world. However, although they are effective as a means of conveying content, they simply cannot replicate the interaction and networking that happens when indexers spend time together. This is an equally important aspect of professional development and the resumption of face-to-face events is eagerly anticipated.